Rupture of gastrointestinal stromal tumor presenting with sudden onset chest and back pain and accompanied by gastric dilatation - Nitta, Kenichi (Acute Med Surg, 2016)
CASE: A 72‐year‐old man with hypertension was admitted with acute‐onset chest and back pain followed by epigastralgia. He was transported by helicopter due to suspected acute aortic dissection. Systolic blood pressures were equal in both arms. Physical examination showed epigastric tenderness without rebound. Blood tests showed leukocytosis. Electrocardiogram and echocardiogram were normal. Abdominal radiography showed acute gastric dilatation with an air‐outlined large mass‐like shadow. Abdominal computed tomography revealed a 6‐cm exophytic mass and large intramural hematoma in the lesser curvature of the gastric body. OUTCOME: The patient underwent urgent laparotomy with total gastrectomy. The resected tumor showed positivity for CD117 and CD34 but negativity for S100, indicating a gastrointestinal stromal tumor. Fourteen days after the surgery, the patient was uneventfully discharged. CONCLUSION: Intramural bleeding of submucosal tumors including gastrointestinal stromal tumor should be considered in cases of acute gastric dilatation. Abdominal radiography may be a clue regarding the presence of this condition.